Triazole-coumarin centered star-shaped polymer: Structural characterizations and electrical properties of graphene composites - Biryan, Fatih (Elsevier, 2020)
In present study, new three arm initiator containing coumarin group and new 4 (3-(4-methoxyphenyl)acryloyl) phenyl acrylate (MPAC) was synthesized. Three-armed star-shaped polymer was obtained by polymerization using ATRP method from the chlorine ends of the initiator. The structure characterization was performed by FT-IR, H-1-NMR, C-13-NMR spectroscopy techniques. Thermal analyzes were performed by using thermogravimetry (TGA) and differential scanning calorimetry analysis (DSC) techniques in a nitrogen atmosphere. Thermal decomposition activation energy (E-a) of star polymer was determined by the Flynn-Wall-Ozawa and Kissinger methods. The average activation energy in the range of 0.02-0.3 conversion range was determined as 115.28 kJ/mol and 152.72 kJ/mol, respectively. Polymer composites were prepared by adding graphene particles in different ratios (0.5%, 1.0%, 2.0%, and 4.0% by weight) to the polymer matrix. The dielectric properties of star polymer and graphene composites were investigated in a range of 100 Hz-20 kHz frequency. Besides, the dielectric properties of the pure polymer were examined as a function of frequency at different temperatures (25 degrees C, 40 degrees C, 55 degrees C, 70 degrees C,). Furthermore, the polymer/4% graphene composite/p-Si thin-film heterojunction diode properties were investigated using current-voltage (I-V) analysis at room temperature in dark. The electrical parameters of heterojunction diode such as the rectification ratio (RR), barrier height (Phi b) and ideality factor (n) were investigated. The frequency dependence of capacitance and the role of interface states were examined. The results showed that chalcone substituted three-arm star polymer/4% graphene composite has a diode and capacitor characteristic. (C) 2020 Elsevier B.V. All rights reserved.
Keywords: Polymer composite; Thermal properties; Kinetic; Electrical properties